2020
DOI: 10.2196/12388
|View full text |Cite
|
Sign up to set email alerts
|

Reflective and Reflexive Stress Responses of Older Adults to Three Gaming Experiences In Relation to Their Cognitive Abilities: Mixed Methods Crossover Study

Abstract: Background The gamification of digital health provisions for older adults (eg, for rehabilitation) is a growing trend; however, many older adults are not familiar with digital games. This lack of experience could cause stress and thus impede participants’ motivations to adopt these technologies. Objective This crossover longitudinal multifactorial study aimed to examine the interactions between game difficulty, appraisal, cognitive ability, and physiolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 98 publications
1
11
0
Order By: Relevance
“…One of the aims of this survey is to address the question of what screen-mediated interventions are needed to respond to the stress caused by the COVID-19 pandemic. Our position is that, in designing and promoting any digital health interventions, we must first ask whether the digitized intervention risks becoming a stressor in and of itself, and then mitigate those risks in design [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the aims of this survey is to address the question of what screen-mediated interventions are needed to respond to the stress caused by the COVID-19 pandemic. Our position is that, in designing and promoting any digital health interventions, we must first ask whether the digitized intervention risks becoming a stressor in and of itself, and then mitigate those risks in design [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process of appraisal is repeated recursively until an individual finds a solution (or fails) [ 23 ]. We have previously proposed a conceptual mixed methods framework for studying interactions between media (such as serious games) and stress [ 27 ]. We repeat this iterative process here by recursively asking questions about sources of actual, perceived, or anticipated stress while investigating individuals’ differences in use and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…On the post-game questionnaire, almost everyone stated that the experience of different sessions (in Phase 1) was enjoyable and interesting (Khalili-Mahani et al 2020). However, some games were more stressful to some than others.…”
Section: Phase 1: What Are the Stressful And Rewarding Aspects Of Gammentioning
confidence: 99%
“…Serious games are also used in the context of health care education to support desirable behavior [ 1 , 4 - 7 ]. The use of games or game-like tasks makes it possible to enhance voluntary engagement and decrease participant drop-out rates [ 8 , 9 ]; in fact, a recent study showed that the experience of playing digital games as compared with standard cognitive tasks was perceived as less stressful [ 10 ]. A high dropout rate, especially in difficult-to-obtain samples, can lead to difficulties interpreting the results, for example, due to decreased statistical power [ 11 - 14 ].…”
Section: Introductionmentioning
confidence: 99%